Mesenchymal Stem Cell Therapies in the Treatment of Musculoskeletal Diseases. Issue 1 (15th January 2014) - Bashir, Jamil; Sherman, Andrew; Lee, Henry; Kaplan, Lee; Hare, Joshua M.
Abstract : The application of regenerative strategies to musculoskeletal ailments offers extraordinary promise to transform management of the conditions of numerous patients. The use of cell‐based therapies and adjunct strategies is under active investigation for injuries and illnesses affecting bones, joints, tendons, and skeletal muscle. Of particular interest to the field is the mesenchymal stem cell, an adult stem cell found in bone marrow and adipose tissue. This cell type can be expanded ex vivo, has allogeneic application, and has the capacity for engraftment and differentiation into mesodermal lineages. Also of major interest in the field is the use of platelet‐rich plasma, a strategy to concentrate endogenous cytokines and growth factors with reparative potential. Here we review the biological basis, clinical studies, safety, and current state of mesenchymal stem cell and platelet‐rich plasma therapies in the treatment of musculoskeletal disease.